Diastolic function assessed my CMR feature tracking is a predictor for outcomes in patients with suspected myocarditis and preserved left ventricular ejection fraction. (13th July 2021) - Bernhard, B; Fischer, K; Stark, AW; Erne, SA; Obrist, SJ; Guensch, DP; Kwong, RY; Graeni, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Diastolic function assessed my CMR feature tracking is a predictor for outcomes in patients with suspected myocarditis and preserved left ventricular ejection fraction Background: Impairment of left ventricular (LV) systolic function was reported to be a valuable predictor for outcomes in patients with myocarditis. However, in patients with myocarditis and preserved LV systolic function, prediction of outcomes remains challenging. So far, minimal data exists about the prognostic role of diastolic function, as assessed by cardiac magnetic resonance imaging (CMR) in the clinical setting of suspected myocarditis. Purpose: To determine the predictive value of LV diastolic function in patients with suspected myocarditis and preserved LV ejection fraction (LVEF). Methods: In patients referred for CMR with clinically suspected myocarditis and LVEF≥50%, diastolic function was assessed by CMR feature tracking (FT). The primary endpoint was defined as a composite of major adverse cardiovascular events (MACE) including hospitalization for heart failure, recurrent myocarditis, sustained ventricular tachycardia and all-cause death. Results: Of 381 patients included with clinically suspected myocarditis (216, 56.7% male, mean age 45.7 ± 16.4 years) late gadolinium enhancement (LGE) was present in 124 (32.4 %) of patients (mean LGE extent 4.9 ± 5.0 g). MACE occurred in 25 (6.6%) individuals at a median follow-up time of 4.5 years. In a univariate cox-regression model, radial, circumferential and longitudinal early diastolic strain rate (EDSR) and circumferential late diastolic strain rate were significantly associated with MACE. After adjustment for age, gender and extent of LGE, radial EDSR remained an independent predictor for MACE (HR = 2.26, 95% CI 1.06 to 4.8; p = 0.034). Conclusion: Diastolic strain rate, as assessed by CMR-FT, can be useful in the prediction of outcomes in patients with myocarditis and preserved LVEF.